(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
During the digitalization of the economy, there is a transformation of many areas of activity. One of such popular areas of activity is marketing. Marketing is an integral part of any business. The main trend of the digital economy is Big Data or Data Science. The potential of Big Data in marketing is colossal, since the data is generated and collected in real time always, and now the marketing industry can see that users are buying, what are their goals, problems and interests. Possessing such data, business can clearly define effective advertising campaigns and sales channels, as well as remove ineffective ones.